Mammoths and the environment - Ukraintseva, Valentina V. (Cambridge University Press, 2013)
"The study of fossilised remains of herbivorous animals, particularly those rare findings with well-preserved gastrointestinal tracts filled with plant remains, is crucial to our understanding of the environment in which they lived. Summarising 30 years of research, Ukraintseva presents evidence on plants once eaten by Siberia's major herbivorous mammals. The collection of pollen and plant spores from food remains sheds light on the vegetation of these ancient habitats, enabling researchers to reconstruct local floras of the time. This also promotes further insight into the causes of the extinction of various species due to changing environmental conditions and food availability. Providing a history of the research undertaken, the book also includes specific chapters on the Cherski horse and bison, along with the vegetation and climate of Siberia in the late Anthropogene period, making it a lasting reference tool for graduate students and researchers in the field"--Resumé vydavatele
Terminologický slovník
Keywords: mamuti; paleoklimatologie -- Sibiř (Rusko); paleobotanika -- Sibiř (Rusko); paleobiogeografie -- Sibiř (Rusko); holocén; environmentální výzkum; evoluce (biologie); mammoths; paleoclimatology -- Siberia (Russia); paleobotany -- Siberia (Russia); paleobiogeography -- Siberia (Russia); holocene; environmental research; evolution (biology); monografie; monographs